Longer Delays in Diagnosis and Treatment of Pulmonary Tuberculosis in Pastoralist Setting, Eastern Ethiopia - Getnet F; Demissie M; Worku A; Gobena T; Tschopp R; Seyoum B (Dove Medical Press, 2020)
Fentabil Getnet,1,2 Meaza Demissie,3 Alemayehu Worku,3,4 Tesfaye Gobena,2 Rea Tschopp,5– 7 Berhanu Seyoum5 1College of Medicine and Health Sciences, Jigjiga University, Jigjiga, Ethiopia; 2School of Public Health, Haramaya University, Harar, Ethiopia; 3Addis Continental Institute of Public Health, Addis Ababa, Ethiopia; 4School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia; 5Armauer Hansen Research Institute, Addis Ababa, Ethiopia; 6Department of Epidemiology and Public Health, Swiss Tropical and Public Health Institute, Basel, Switzerland; 7University of Basel, Basel, SwitzerlandCorrespondence: Fentabil GetnetJigjiga University, P. O. Box 1020, Jigjiga, EthiopiaTel +251 913 289 380Email b.infen4ever@gmail.comPurpose: This study aimed to assess the extent of patient, health system and total delays in diagnosis and treatment of pulmonary tuberculosis (TB) in Somali pastoralist setting, Ethiopia.Patients and Methods: A cross-sectional study among 444 confirmed new pulmonary TB patients aged ≥ 15 years in 5 TB care units was conducted between December 2017 and October 2018. Data were collected using a structured questionnaire and record review. We measured delays from symptom onset to provider visit, provider visit to diagnosis and diagnosis to treatment initiation. Delays were summarized using median days. Mann–Whitney and Kruskal–Wallis tests were used to compare delays between categories of explanatory variables. The Log-binomial regression model was used to reveal factors associated with health system delay ≥ 15 days, presented in adjusted prevalence ratio (APR) with 95% confidence interval (CI).Results: The median age of patients was 30 years, ranged from 15 to 82. The majority (62.4%) were male, and nearly half (46.4%) were pastoralists. The median patient, health system and total delays were 30 (19– 48.5), 14 (4.5– 29.5) and 50 (35– 73.5) days, respectively. The median patient delay (35.5 days) and total delay (58.5 days) among pastoralists were substantially higher than the equivalent delays among non-pastoralists [p< 0.001]. Of all, 3.8% of patients (16 of 18 were pastoralists) delayed longer than 6 months without initiating treatment. Factors associated with health system delay ≥ 15 days were mild symptoms [APR (95% CI) = 1.4 (1.1– 1.7)], smear-negativity [APR (95% CI) = 1.2 (1.01– 1.5)], first visit to health centers [APR (95% CI) = 1.6 (1.3– 2.0)] and multiple provider contacts [APR (95% CI) = 5.8 (3.5– 9.6)].Conclusion: Delay in diagnosis and treatment remains a major challenge of tuberculosis control targets in pastoralist settings of Ethiopia. Efforts to expand services tailored to transhumance patterns and diagnostic capacity of primary healthcare units need to be prioritized.Keywords: patient delay, health system delay, total delay, tuberculosis, pastoralist